The Role of Poetic Style In Correcting Phonetic Pronunciation: From Poetic Play To Phonetic Play - Abdullaeva Nilufar (Indonesian Journal of Innovation Studies, 2022)
One of the important tasks at any stage of teaching a foreign language, including French, is to maintain and improve pronunciation skills. The phonetic process that facilitates the formation of such skills is rhyme.